INTRODUCTION TO SOCIETY REGISTER - Mariusz Baranowski; Anna Odrowąż-Coates (Society Register)
In this issue, one may find both theoretical and empirical papers, followed by three book reviews. The issue opens with papers in English, which is our target language, followed by papers in Polish. There are papers from authors based in Algeria, India, Iran, UK, USA, Vietnam, Turkey and Poland, who are all social researchers and active observers of social life at different stages of their academic and professional career. We present you with a selection of current social, educational, political and philosophical topics in a socio-historical context: intercultural issues, identity and resistance, social systems, social control and rehabilitation, communication, reflexivity, spirituality and religion, social justice, issues relevant to education and care, politics, language and even poetry. We aim to become an open forum of scientific thought exchange, inviting scholars with a wide range of experience within the rich field of social sciences, embracing subjects that are both central and peripheral to the further development of disciplines such as sociology, comparative pedagogy, social psychology, anthropology, education, social policy, international relations and philosophy. What makes us unique in Central Europe is that we wish to offer avenues to be heard and visible for early career scholars alongside established authorities in these fields of expertise. We would like to be comprehensive internationally and in order to do so we promote comparative studies.